Problem-based learning approach enhances the problem solving skills in Chemistry of high school students - Joseph Valdez; Melfei Bungihan (OmniaScience, 2019)
The study aimed to investigate the effectiveness of problem-based learning (PBL) approach in enhancing the problem solving skills in Chemistry of Grade 9 students in a public high school in the Philippines. The level of problem solving skills of the students in the non-PBL and PBL group before and after their exposure to non-PBL and PBL approaches was determined respectively. The comparison of their levels before and after the intervention was done to determine the effectiveness of the non-PBL and PBL approaches. Then comparison of the effectiveness of non-PBL and PBL approach was assessed. Using the descriptive-comparative and pretest-posttest experimental design in processing the data from 96 students, the following revelations were obtained: (1) the level of problem solving skills before and after their exposure to non-PBL approach is generally very low; (2) the level of problem solving skills was initially very low but was comparatively increased to low after exposure to PBL; (3) there was a significant difference in the level of problem solving skills of the students in the PBL group; (4) between these two approaches in this study, the PBL approach of teaching the chemistry concepts to Grade 9 students was proven more effective than the non-PBL approach.